A new species of the leafhopper genus Naevus Knight, 1970 (Hemiptera: Cicadellidae: Deltocephalinae: Opsiini), from Saudi Arabia - El-Sonbati, Saad A.; Wilson, Michael R.; Dhafer, Hathal M. Al (Zootaxa, 2015)
The genus Naevus Knight, 1970 is recorded from the mountains of southwestern Saudi Arabia, the first record from the Arabian Peninsula. A new species, Naevus hathali El-Sonbati & Wilson sp. n. is described here, which appears to have an asymmetric aedeagus. An illustrated key to Naevus species is presented to facilitate identification.